Kwashiorkor and sarcopenic obesity: Two Sides Of The Same Coin? - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Kwashiorkor is a form of protein energy malnutrition, while obesity usually occurs due to overnutrition. These syndromes, therefore, are considered to be poles apart. However, there are many similarities, between the two conditions. Both are forms of malnutrition, and have common features in causation, clinical presentation, comorbidities and complications, as well as strategies for management. In this review, we discuss whether kwashiorkor and obesity, especially sarcopenic obesity, are two sides of the same coin or not. Keywords: Kwashiorkor, Sarcopenia, Sarcopenic obesity, Protein energy malnutrition.